The Effect Of Education, Income, Lifestyle And Taxation Sanctions On The Awareness Of Motor Vehicles Tax Payers In Sidenreng Rappang District - Fatimah Fatimah; Arham Arham; Cica Ibrahim (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the effect of education, income, lifestyle and tax sanctions on the awareness of motor vehicle taxpayers in Sidenreng Rappang Regency. It is hoped that the results of this research can become material for scientific research in the field of regional financial accounting, especially for reviewers of taxpayers' understandings in Sidenreng Rappang Regency regarding motor vehicle tax payments. The research was conducted at the SAMSAT office of Sidenreng Rappang Regency. The data collection techniques used in this study were observation, recording and questionnaire surveys. The sample of this study was 94 motor vehicle taxpayers in Sidenreng Rappang Regency as respondents. The data analysis technique in this study used multiple linear regression analysis with the help of the Windows version 20 SPSS (Static Product and Service Support) application. The results showed that based on the analysis carried out there was a significant, simultaneous and partial influence between education, income, lifestyle and tax sanctions on the awareness of motor vehicle taxpayers in Sidenreng Rappang Regency.